Emotional Regulation and Emotional Intelligence of Early Childhood Education Teachers - Agustin Atmaningrum; Nuratthahirah Ansar (Indonesian Journal of Educational Studies, 2026)
Abstract. This study aimed to examine the improvement of Early Childhood Education (ECE) teachers’ understanding of emotion regulation and emotional intelligence after participating in a psychoeducational program. The study employed a quantitative approach using a one-group pretest–posttest design. The participants consisted of 43 ECE teachers who completed the psychoeducational program. The research instrument was a multiple-choice knowledge test administered before and after the intervention. Data were analyzed using the Wilcoxon Signed-Ranks Test with the assistance of SPSS. The results revealed a statistically significant difference between pre-test and post-test scores, with a Z value of -2.814 and a significance level of p = 0.005. Descriptive findings showed that 11 participants experienced an increase in their scores, 1 participant showed a decrease, and 31 participants obtained unchanged scores. These findings indicate that psychoeducation on emotion regulation and emotional intelligence contributed significantly to improving some ECE teachers' understanding. However, the large number of participants with unchanged scores suggests that the improvement in understanding was not evenly distributed and requires further reinforcement through practical activities, case simulations, reflection on teaching experiences, and continuous mentoring. Therefore, psychoeducation on emotion regulation and emotional intelligence can serve as an initial strategy for strengthening ECE teachers’ capacity to foster warm, safe, empathetic, and supportive learning interactions that promote young children's social-emotional development. Keywords: emotion regulation; emotional intelligence; early childhood education teachers; psychoeducation; pretest–posttest design.